Total ossicular replacement prosthesis of the middle ear: a biomechanical analysis - Gentil, Fernanda (2015)
The main goal of the present study is to analyze and characterize the behavior of the middle ear, when a total ossicular replacement prosthesis (TORP) is used in the ossicular chain, in order to troubleshoot conductive hearing loss. Using a finite element model (FEM), a dynamic study of the middle ear was made. The displacement values were obtained at the umbo and stapes footplate, for a sound pressure level of 80 dB sound pressure level (SPL) applied at the tympanic membrane, when a cartilage in membrane-prosthesis interface of different diameters and thicknesses was used. The results were compared with the healthy middle ear model. The usage of this model aims to achieve a set of techniques that promotes the best possible performance of prosthesis in the middle ear. The present study allows to conclude that the rehabilitation of the middle ear with TORP can lead to the best results when used with 4 mm diameter cartilages, with a thin thickness of 0.3 mm.